Post-Christmas Blues: A Rare Cause of Cyanosis - Laurie Barron; H Jay Biem (Canadian Respiratory Journal)
A patient was referred for urgent evaluation of cyanosis. Although she had symptoms and signs of an upper respiratory tract infection, she had a normal cardiorespiratory examination and normal transcutaneous oxygen saturation. Further evaluation revealed a benign cause for the cyanosis.